Identification of the new HLA‐DPB1 allele, DPB1*647:01, in an Italian patient with leukemia. (26th February 2018) - Fornaciari, S.; Sciarrino, R.; Biagini, C.; Mariotti, M. L.; Curcio, M.
Abstract : A novel HLA‐DPB1 allele, named HLA‐DPB1*647:01, identified in a leukemia patient.